Evaluation of Skin to Stone Distance by Non-Contrast Computed Tomography as an Independent Predictor of Stone-Free Rate of Extra-Corporeal Shockwave Lithotripsy for Renal Pelvic Stones - Khalid Islam, Syed Ameroon Shah, Nasrum Minallah, Naseeb Dad, Faheem Ullah, Shabeena Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Pakistan is situated in the Afro-Asian stone belt. We come across a vast majority of patients having renal calculi. The treatment of renal stones has evolved from open surgery to extracorporeal shock wave lithotripsy (ESWL), percutaneous nephrolithotomy (PCNL) and retrograde intrarenal surgery (RIRS) in past 20 years. Objective: To determine mean skin to stone distance (SSD) in patients undergoing ESWL for renal pelvic stones and to compare mean SSD between patients with successful ESWL and failed ESWL outcomes for renal pelvic stones. Subjects and Methods: This descriptive case series study was carried out in the Department of Urology, Institute of Kidney Diseases Hayatabad Medical Complex Peshawar from September 2017 to March 2018. A total of 50 patients with renal pelvic stones were enrolled for the study. After consent, non-contrast computed tomography of the kidney ureter and blabber (NCCT KUB) was performed and SSD was measured. All patients underwent ESWL. The patient status either as stone free or having residual stones based on NCCT KUB result was noted on 3rd month. Patients having no stone fragments were defined as stone free and the procedure was defined as successful. Results: The mean age of the patients was 39.02 +/- 12.16 years. 33 (66%) were male and 17 (34%) were female. ESWL was successful in 39 (78%) of patients. 11 (22%) of the patients had residual stones. The mean SSD in patients with successful ESWL outcome was significantly lower than the patients with failed ESWL outcome (10.9 +/- 3.0 vs 14.8 +/- 1.8 cm, p-value = 0.001) Practical Implication: The study results will help the urologists in deciding appropriate treatment modality for patients with renal pelvic stones. Conclusion: We conclude that SSD is lower in patients with successful outcome of ESWL in comparison to those with failed outcome. Therefore pre-treatment NCCT KUB should be used in patients with renal stones to determine the SSD which might predict the outcomes of ESWL. Keywords: Renal calculi, Skin to stone distance, extracorporeal shockwave lithotripsy.